Dental and oral nonmetric traits in a Coimbra reference sample: testing intrasample chronological and spatial variation - Marado, Luís Miguel (2019)
A reference sample of dental and oral nonmetric traits should represent its biological population from which it stems. The presence of individuals born at different times, different regions, and separate countries in the Coimbra-identified cranial collections provides the test of whether this sample reflects the biological continuity of this Portuguese sample among the late modern (early industrialization, nineteenth century) to early contemporary (early demographic transition, first half of the twentieth century) population of this region of central Portugal. The Coimbra collections were scored for 61 traits using methodology by Hauser and De Stefano (1989), Turner et al. (1991), Scott and Turner (1997), Irish (1998), and Marado and Silva (2016). The 600 individuals in the sample were divided by generation, region, and nationality. Their phenetic diversity was tested with principal component analysis and with the mean measure of divergence statistic. The proximity between the subsamples was generalized, and it mimicked previous genetic marker results Some small subsamples hindered conclusions; nevertheless, this Coimbra sample is considered a reliable dental reference sample for the Portuguese late modern/early contemporary population.